Preparation and mechanical properties of short carbon fibers reinforced α-Al2O3-based composites. Issue 16 (November 2018) - Jia, Jiangang; Liu, Diqiang; Gao, Changqi; Ji, Genshun; Guo, Tieming
Abstract: Short carbon fiber (Csf ) reinforced α-Al2 O3 (Csf /α-Al2 O3 ) composites were fabricated by a sol-gel dispersing method and a subsequent hot-pressing process. Effects of dispersing method, fiber contents and sintering aids on the mechanical performance of the composites were investigated. Based on sol-gel strategy, series of Csf /α-Al2 O3 composites were prepared and the Csf was evenly dispersed in the matrix of α-Al2 O3 and preserved its pristine smooth surface, much superior to that of Csf /α-Al2 O3 prepared using ball milling method where Csf was seriously damaged. The flexural strength of Csf /α-Al2 O3 composites first increase and reach the peak values, then decrease with the increase in fiber content. It reaches the maximum value of 336 MPa at 5 vol% of Csf, 106.0% higher than that of the α-Al2 O3 ceramic without Csf . The fracture toughness increases with Csf content and deliver the highest value of 7.1 MPa/m 2 at 15 vol% of Csf, 117.4% higher than that of the α-Al2 O3 ceramic without Csf (3.5 MPa/m 2 ). Fiber bridging, debonding and pulling out can effectively deflect the crack and release the stress intensity at the tip of the crack, resulting in the significant reinforcing and toughening effect in Csf /Al2 O3 composites. It should be mentioned that the tensile strength of the carbon fiber drastically decreases from about 2800 MPa to about 1200 MPa after heat-treated at 1500 ℃ for 1 h indicating that the potential of carbon fiber reinforcement is not fully exploited.